Multi-component antioxidant for carbon-containing refractory material, preparation method and carbon-containing refractory material
By using multiple oxidant inhibitors in refractory materials, the problem of low antioxidant performance of existing oxidant inhibitors is solved, and a more efficient oxidation inhibition effect is achieved, cost is reduced, and the recycling rate of the material is improved.
Patent Information
- Application Number
- CN202411873652.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing oxidation resistance of the existing oxidation resistance is not high in refractory materials, and it will form an oxide film during use, affecting the material performance.
A multivariate oxidation inhibitor is proposed, which includes 50-80% by weight of metal element, 10-20% by weight of oxide, 10-20% by weight of carbide and 0-8% by weight of graphite powder in mass ratio, and is prepared by stirring and mixing to form a dense protective film to improve oxidation resistance.
Effectively inhibit the formation of oxidative decarbonization layers, improve the oxidation resistance of carbon-containing refractory materials, reduce oxidation rate, extend service life, reduce material loss and production costs, and improve waste utilization.
Smart Images

Figure CN119684012A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of refractory materials, and in particular to a multi-element antioxidant for carbon-containing refractory materials, a preparation method and the carbon-containing refractory materials. Background Art
[0002] In order to prevent the oxidation of carbon-containing refractory materials, it is often necessary to introduce antioxidants into the materials. The mechanism of action is as follows: at the operating temperature, the antioxidant reacts with oxygen before carbon, and the volume increases after the reaction, forming a dense protective film on the surface of the green body, thereby increasing the density of the green body and increasing the difficulty of the reaction between oxygen atoms and carbon.
[0003] At present, the antioxidants used in the market are mostly metallic silicon or silicon carbide, and aluminum powder. During the actual use of refractory materials, they will form oxide films, which will affect the oxidation resistance to a certain extent and have a high cost. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a multi-element antioxidant for carbon-containing refractory materials, a preparation method and a carbon-containing refractory material, so as to solve the problem that the existing antioxidants have low antioxidant performance.
[0005] In one aspect of the present invention, a multi-component antioxidant for carbon-containing refractory materials is provided, which comprises, by mass ratio, 50-80wt% of a metal element, 10-20wt% of an oxide, 10-20wt% of a carbide and 0-8wt% of graphite powder, wherein the metal element is at least one of aluminum, silicon and magnesium, the oxide is at least one of aluminum oxide, chromium oxide, magnesium aluminum spinel and lanthanum oxide, and the carbide is at least one of silicon carbide and boron carbide.
[0006] Optionally, the particle size of the aluminum is 65-125 μm, the particle size of the silicon is 25-75 μm, the particle size of the magnesium is 25-60 μm, and the particle size of the graphite powder is 44 μm.
[0007] Optionally, the alumina is one or more combinations of corundum fine powder, α-Al2O3 micropowder, β-Al2O3 micropowder, and γ-Al2O3 micropowder, wherein the particle size range of the corundum fine powder is 51-70μm, the particle size range of the α-Al2O3 micropowder is 10-20μm, the particle size range of the β-Al2O3 micropowder is 15-25μm, and the particle size range of the γ-Al2O3 micropowder is 15-30μm.
[0008] Optionally, the mass ratio of the lanthanum oxide is 0-5wt%, and the particle size range is 30-75μm.
[0009] Optionally, the silicon carbide has a particle size range of 100-200 μm.
[0010] Optionally, the mass ratio of the boron carbide is 0-0.5wt%, and the particle size range is 30-75μm.
[0011] Another aspect of the present invention provides a method for preparing a multi-element antioxidant for a carbon-containing refractory material, comprising the following steps:
[0012] Batching according to mass components;
[0013] Stir and mix the powdered metal element and the powdered oxide for 8-12 minutes;
[0014] Powdered carbide and powdered graphite are added and stirred and mixed, and the total stirring time is controlled within 40-60 minutes.
[0015] Furthermore, the stirring and mixing is carried out under sealed conditions, and the temperature is controlled at 10-30°C.
[0016] Another aspect of the present invention provides a carbon-containing refractory material, comprising 0-2.5wt% of a multi-component antioxidant, 3wt% of a binder, 20-25wt% of 98 fused magnesia 5-3mm, 20-30wt% of 98 fused magnesia 3-1mm, 15-20wt% of 98 fused magnesia 1-0mm, 10-20wt% of 98 fused magnesia 200 mesh, and 12-20wt% of flake graphite.
[0017] Optionally, the binder is liquid phenolic resin.
[0018] The beneficial effects of the present invention are as follows: the carbon-containing refractory material to which the multi-element antioxidant proposed by the present invention is added has a little change in the loss on ignition rate and a significantly reduced thickness of the oxide layer. Compared with the prior art, the multi-element antioxidant of the present invention can effectively inhibit the formation of an oxidative decarburization layer, thereby improving the oxidation resistance of the carbon-containing refractory material, reducing the oxidation rate of the carbon-containing refractory material to about 20% of the original, reducing the decarburization layer caused during baking, increasing the service life of the lining of key metallurgical components such as a refining ladle, a converter, and an electric arc furnace, reducing the loss of refractory materials, and reducing the cost of steelmaking and carbon-containing refractory materials. At the same time, part of the aggregate used in the production of the refractory material proposed by the present invention comes from the waste of recycled magnesium-carbon refractory bricks. Compared with the traditional formula, the waste utilization rate of the refractory material proposed by the present invention is increased by 20%, the resource recycling rate of the refractory material is increased, and the production cost of the refractory material is further reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 is the XRD spectrum of the antioxidant proposed by the present invention;
[0021] Figure 2 This is a microstructure diagram of the antioxidant proposed in the present invention. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.
[0024] Example 1
[0025] A multi-element antioxidant for carbon-containing refractory materials comprises: a powdered metal element weighed at a component ratio of 50wt%, wherein aluminum and silicon are mixed at a mass ratio of 4:5 in the metal element, the particle size of aluminum is 125μm, and the particle size of silicon is 35μm; a powdered oxide is weighed at a component ratio of 22wt%, wherein aluminum oxide, magnesium aluminum spinel and lanthanum oxide are mixed at a mass ratio of 3:6:1 in the oxide, wherein the ratio of corundum fine powder, α-Al2O3 micropowder, β-Al2O3 micropowder and γ-Al2O3 micropowder in the aluminum oxide is 8:2:1:1, the corundum fine powder The particle size of α-Al2O3 micropowder is 55μm, the particle size of α-Al2O3 micropowder is 12μm, the particle size of β-Al2O3 micropowder is 18μm, and the particle size of γ-Al2O3 micropowder is 20μm; the particle size of magnesia alumina spinel fine powder is 74μm, and the particle size of lanthanum oxide is 35μm; powdered carbide is weighed at a component ratio of 20wt%, and silicon carbide and boron carbide are proportioned in a mass ratio of 10:1 in the carbide, the particle size range of boron carbide is 74μm, and the particle size of silicon carbide is 120μm; powdered graphite is weighed at a component ratio of 8wt%, and the particle size of graphite is 44μm.
[0026] First, the powdered metal element and the powdered oxide are placed in a sealed environment of a mixer and mixed. The speed of the mixer is controlled at 60 rpm and the temperature is controlled at 15°C. After stirring for 10 minutes, carbide and graphite powder are added and stirred. After stirring for another 30 minutes, a powdered antioxidant product is obtained.
[0027] The XRD spectrum of the antioxidant prepared by the present invention is as follows: Figure 1 As shown in the figure, the 200-fold microstructure is shown in Figure 2 shown.
[0028] Example 2
[0029] A multi-element antioxidant for carbon-containing refractory materials comprises: a powdered metal element weighed at a component ratio of 65wt%, wherein aluminum and silicon are mixed at a mass ratio of 7:3 in the metal element, the particle size of aluminum is 160 mesh, and the particle size of silicon is 600 mesh; a powdered oxide is weighed at a component ratio of 15wt%, wherein aluminum oxide, chromium oxide and lanthanum oxide are mixed at a mass ratio of 8:1:1 in the oxide, wherein the ratio of corundum fine powder, α-Al2O3 micropowder and β-Al2O3 micropowder in the aluminum oxide is 8:2:1, the particle size of the corundum fine powder is 60μm, the particle size of the α-Al2O3 micropowder is 15μm, the particle size of the β-Al2O3 micropowder is 20μm, the particle size of the chromium oxide is 30μm, and the particle size of the lanthanum oxide is 35μm;
[0030] Powdered carbide is weighed at a component ratio of 15wt%, in which silicon carbide and boron carbide are mixed at a mass ratio of 10:1, the particle size range of boron carbide is 74μm, and the particle size of silicon carbide is 120μm; powdered graphite is weighed at a component ratio of 5wt%, and the particle size of graphite is 44μm.
[0031] First, the powdered metal element and powdered oxide are placed in a sealed environment of a mixer for mixing. The speed of the mixer is controlled at 80 rpm and the temperature is controlled at 25°C. After stirring for 12 minutes, carbide and graphite powder are added and stirred. After stirring for another 40 minutes, a powdered antioxidant product is obtained.
[0032] Example 3
[0033] A multi-element antioxidant for carbon-containing refractory materials comprises: a powdered metal element weighed at a component ratio of 78wt%, wherein aluminum, silicon and magnesium are mixed at a mass ratio of 7:2:1, the particle size of aluminum is 125μm, the particle size of silicon is 35μm, and the particle size of magnesium is 50μm; a powdered oxide is weighed at a component ratio of 10wt%, wherein aluminum oxide and chromium oxide are mixed at a mass ratio of 8:2, wherein the fine corundum powder and α-A in the aluminum oxide are mixed at a mass ratio of 1 ... The ratio of l2O3 micro powder is 6:4, the particle size of corundum fine powder is 55μm, and the particle size of α-Al2O3 micro powder is 12μm; the particle size of chromium oxide is 30μm; powdered carbide is weighed at a component ratio of 7wt%, among which silicon carbide and boron carbide are proportioned at a mass ratio of 10:1, the particle size range of boron carbide is 74μm, and the particle size of silicon carbide is 120μm; powdered graphite is weighed at a component ratio of 5wt%, and the particle size of graphite is 44μm.
[0034] First, the powdered metal element and the powdered oxide are placed in a sealed environment of a mixer and mixed. The speed of the mixer is controlled at 60 rpm and the temperature is controlled at 15°C. After stirring for 10 minutes, carbide and graphite powder are added and stirred. After stirring for another 30 minutes, a powdered antioxidant product is obtained.
[0035] The multi-component antioxidant proposed in the present invention is used as an additive to prepare a carbon-containing refractory material. The carbon-containing refractory material includes, according to the component ratio, 0-2.5wt% of the multi-component antioxidant, 3wt% of a binder, 20-25wt% of 98 fused magnesia 5-3mm, 20-30wt% of 98 fused magnesia 3-1mm, 15-20wt% of 98 fused magnesia 1-0mm, 10-20wt% of 98 fused magnesia 200 mesh, and 12-20wt% of flake graphite.
[0036] Example 4
[0037] The materials are mixed according to the ratio of 25wt% of 98 fused magnesia 5-3mm, 25wt% of 98 fused magnesia 3-1mm, 15wt% of 98 fused magnesia 1-0mm, 19.5wt% of 98 fused magnesia 200 mesh, 15wt% of flake graphite, 0.5wt% of multi-component antioxidant and 3wt% of liquid phenolic resin, and the mixed materials are pressed into a green body with a length of 50.38mm, a width of 49.88mm and a height of 50.20mm.
[0038] Example 5
[0039] The materials are mixed according to the ratio of 22wt% of 98 fused magnesia 5-3mm, 28wt% of 98 fused magnesia 3-1mm, 17wt% of 98 fused magnesia 1-0mm, 19wt% of 98 fused magnesia 200 mesh, 13wt% of flake graphite, 1wt% of multi-component antioxidant and 3wt% of liquid phenolic resin, and the mixed materials are pressed into a green body with a length of 50.20mm, a width of 50.18mm and a height of 50.33mm.
[0040] Example 6
[0041] The materials are mixed according to the ratio of 25wt% of 98 fused magnesia 5-3mm, 25wt% of 98 fused magnesia 3-1mm, 17wt% of 98 fused magnesia 1-0mm, 13wt% of 98 fused magnesia 200 mesh, 18wt% of flake graphite, 2wt% of multi-component antioxidant and 3wt% of liquid phenolic resin, and the mixed materials are pressed into a green body with a length of 49.99mm, a width of 50.18mm and a height of 50.10mm.
[0042] Comparative Example 1
[0043] A multi-element antioxidant for carbon-containing refractory materials is prepared according to a component ratio of 60wt% of metal elemental aluminum, 20wt% of metal elemental silicon and 20wt% of silicon carbide, wherein the particle size of aluminum is 120μm, the particle size of silicon is 60μm and the particle size of silicon carbide is 100μm. The above powders are weighed according to the proportion and then put into a sealed environment of a mixer for mixing. The speed of the mixer is controlled at 100 rpm and the temperature is controlled at 30°C. After stirring for 10 minutes, carbides are added for stirring. After stirring for 50 minutes, a powdery antioxidant product is obtained. The antioxidant prepared in the example is added into the refractory material for billet making, and the materials are mixed according to the ratio of 25wt% of 98 fused magnesia 5-3mm, 25wt% of 98 fused magnesia 3-1mm, 17wt% of 98 fused magnesia 1-0mm, 13wt% of 98 fused magnesia 200 mesh, 18wt% of flake graphite, 2wt% of conventional antioxidant (1wt% aluminum + 1wt% silicon), and 3wt% of liquid phenolic resin. The mixed material is pressed into a billet with a length of 50.46mm, a width of 50.08mm, and a height of 49.68mm.
[0044] Comparative Example 2
[0045] A refractory material is prepared by mixing 25wt% of 98 fused magnesia 5-3mm, 25wt% of 98 fused magnesia 3-1mm, 17wt% of 98 fused magnesia 1-0mm, 15wt% of 98 fused magnesia 200 mesh, 18wt% of flake graphite and 3wt% of liquid phenolic resin, and pressing the mixed material into a green body with a length of 50.02mm, a width of 50.10mm and a height of 50.23mm.
[0046] Examples 4, 5, 6 and Comparative Examples 1 and 2 were subjected to an antioxidant comparison test.
[0047] The test method is:
[0048] The above sample was placed in an electric heating furnace, and air was introduced into the furnace at a rate of 260 liters / hour. The electric heating furnace was started to heat up, and the temperature was raised to 1100°C within 1 hour. The furnace was stopped after keeping warm for 3 hours. Air was continued to be introduced for 3 hours after stopping the furnace. When the furnace temperature dropped to 500°C, the air was stopped and the sample was removed. After the sample was cooled, it was weighed, the external dimensions of the sample were measured, the sample was cut in the middle, and the thickness of the oxide layer was measured. The measurement data are shown in Table 1.
[0049] Table 1
[0050]
[0051] Based on the measured data in Table 1, the data of the burning loss rate and oxidation rate of Examples 4-6 and Comparative Examples 1-2 are calculated as shown in Table 2.
[0052] Table 2
[0053] Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Loss on ignition rate (%) 8.72 6.27 4.35 9.89 12.47 Oxidation rate (%) 16.76 11.91 6.94 21.25 32.59
[0054] The calculation formula of oxidation rate is oxidation rate = [1-(unoxidized portion length * unoxidized portion width) / (burned length * burned width)]*100%, and loss on burn rate = (1-burned weight / pre-burned weight)*100%.
[0056] It can be seen from the above measurement data that the carbon-containing refractory material to which the multi-element antioxidant proposed in the present invention is added has little change in the loss on burnout rate and a significantly reduced thickness of the oxide layer. Compared with the prior art, the multi-element antioxidant of the present invention can effectively inhibit the formation of an oxidative decarburization layer, thereby improving the oxidation resistance of the carbon-containing refractory material, reducing the oxidation rate of the carbon-containing refractory material to about 20% of the original, reducing the decarburization layer caused during baking, increasing the service life of the lining of key metallurgical components such as refining ladles, converters, and electric arc furnaces, reducing refractory material loss, and reducing the cost of steelmaking and carbon-containing refractory materials. At the same time, part of the aggregate used in the production of the refractory material proposed in the present invention comes from the waste of recycled magnesium-carbon refractory bricks. Compared with the traditional formula, the waste utilization rate of the refractory material proposed in the present invention is increased by 20%, the resource recycling rate of the refractory material is increased, and the production cost of the refractory material is further reduced.
[0057] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A multi-element antioxidant for carbon-containing refractory materials, characterized in that: The invention comprises 50-80wt% of a metal element, 10-20wt% of an oxide, 10-20wt% of a carbide and 0-8wt% of graphite powder in a mass ratio, wherein the metal element is at least one of aluminum, silicon and magnesium, the oxide is at least one of aluminum oxide, chromium oxide, magnesium aluminum spinel and lanthanum oxide, and the carbide is at least one of silicon carbide and boron carbide.
2. The multi-element antioxidant for carbon-containing refractory materials according to claim 1, characterized in that: The particle size of the aluminum is 65-125 μm, the particle size of the silicon is 25-75 μm, the particle size of the magnesium is 25-60 μm, and the particle size of the graphite powder is 44 μm.
3. The multi-element antioxidant for carbon-containing refractory materials according to claim 1, characterized in that: The alumina is one or more combinations of corundum fine powder, α-Al2O3 micropowder, β-Al2O3 micropowder, and γ-Al2O3 micropowder, wherein the particle size range of the corundum fine powder is 51-70 μm, the particle size range of the α-Al2O3 micropowder is 10-20 μm, the particle size range of the β-Al2O3 micropowder is 15-25 μm, and the particle size range of the γ-Al2O3 micropowder is 15-30 μm.
4. The multi-element antioxidant for carbon-containing refractory materials according to claim 1, characterized in that: The mass ratio of the lanthanum oxide is 0-5wt%, and the particle size range is 30-75μm.
5. The multi-element antioxidant for carbon-containing refractory materials according to claim 1, characterized in that: The particle size of the silicon carbide is in the range of 100-200 μm.
6. The multi-element antioxidant for carbon-containing refractory materials according to claim 1, characterized in that: The mass ratio of the boron carbide is 0-0.5wt%, and the particle size range is 30-75μm.
7. A method for preparing the multi-element antioxidant for carbon-containing refractory materials according to any one of claims 1 to 6, comprising the following steps: Batching according to mass components; Stir and mix the powdered metal element and the powdered oxide for 8-12 minutes; Powdered carbide and powdered graphite are added and stirred and mixed, and the total stirring time is controlled within 40-60 minutes.
8. The preparation method according to claim 7, characterized in that: The stirring and mixing is carried out under sealed conditions and the temperature is controlled at 10-30°C.
9. A carbon-containing refractory material, characterized in that: The invention comprises 0-2.5wt% of the multi-anti-oxidant according to any one of claims 1-6, 3wt% of a binder, 20-25wt% of 98 fused magnesia 5-3mm, 20-30wt% of 98 fused magnesia 3-1mm, 15-20wt% of 98 fused magnesia 1-0mm, 10-20wt% of 98 fused magnesia 200 mesh, and 12-20wt% of flake graphite.
10. The carbon-containing refractory material according to claim 9, characterized in that: The binder is liquid phenolic resin.